Simulation Analysis of Gas Bubble Formation and Escape in Non-Newtonian Drilling Fluids. (9th April 2021) - Zhao, Xinxin; Yan, Xiangzhen; Jiang, Hongwei; Yang, Guang; Wang, Jintang; Sun, Xiaohui; Gao, Yonghai; Yin, Faling
Abstract : In this study, the formation and escape movements of a bubble injected in non-Newtonian drilling fluid through a pore were numerically simulated using a volume of fluid method. The pattern of a single bubble and the pressure and velocity fields of the surrounding liquid phase during the bubble formation were analyzed and compared with experimental results; based on the comparison, the formation and escape properties of the bubble were further studied. In particular, the effects of static shear force, consistency coefficient, and flow behavior index on the growth and escape time of the bubble were analyzed. The results show that, owing to the effect of velocity on the viscosity of a non-Newtonian drilling fluid, the escape time and volume of the bubble increase with an increase in static shear force, consistency coefficient, and flow behavior index. Among the three parameters, the flow behavior index has the greatest effect. This is because the shear disturbance of a bubble to its surrounding fluid during its growth and escape, caused by the shear thinning of a yield-power-law fluid, reduces the fluid viscosity. The shear thinning decreases, and the resistance to the bubble increases as the flow behavior index approaches 1, leading to larger bubble formation times and separation volumes. An empirical formula for predicting the equivalent radius of bubbles considering the liquid yield stress, inertial force, viscous force, and surface tension is established. The average error of predicting the equivalent radius of detached bubble is 0.80%, which can provide a reference for the better study of bubble migration and flow pattern in non-Newtonian fluid.